Investigating the effect of tetracycline on gut microbiome metabolism and microbe-host interactions - Keerthisinghe, Rajapaksha Pathiranage Tharushi Prabha (Nanyang Technological University, 2021)
Tetracycline (TET) is an extensively used antibiotic for human therapeutic purposes and veterinary medicine. Extensive use in a wide range of applications leads to the frequent occurrence of TET in aquatic environments. Thus, there is a higher possibility for the aquatic organisms inhabiting those environments to expose to TET. Effects of TET on aquatic organisms such as freshwater fish species have been studied, mostly focusing on toxic effects at embryonic and larval stages. However, limited information is available on the possible long-term effect of TET exposure on aquatic fishes at the juvenile stage, especially at low or environmentally relevant levels. Moreover, studying the simultaneous impacts on aquatic organisms and their gut microbiome exposed to chemicals as well as their correlation is rare, even though it has been done for some rodent models. This thesis first started by investigating the effects of long-term TET exposure on zebrafish (Danio rerio). The study exposed zebrafish at the juvenile stage to two different low levels of TET for a one-month period until their adulthood. Subsequently, the study analyzed the growth (i.e., body weight and length) and liver characteristics (i.e., histology, gene expression, lipidome, and metabolome) of zebrafish. In addition, the study also examined the alterations in zebrafish gut microbial community. The results revealed an interesting observation of increased body weight gain and liver lipid accumulation in zebrafish upon TET exposure, along with substantial changes in the gut microbiome with an increase in known obesogenic microbial factors. Hence, a hypothesis can be generated to link the observed host effects in zebrafish to the TET mediated gut microbiome dysbiosis. Thus, the next sections of the thesis have more focus on the gut microbiome. Accordingly, TET induced gut microbiome changes that may possibly be associated with host weight gain were investigated using a few approaches: TET induced metabolic change in a few representative pure gut bacterial strains; TET caused metabolic consequences in an in vitro gut microbiome secretome; and the contribution of TET affected metabolic and immunological gut microbiome-host interactions to obesity-related complications. Thus, the second part of the thesis investigated the TET induced metabolic alteration in model gut bacteria. This study used three model gut bacteria including Bacteroides fragilis, Clostridium sporogenes, and Escherichia coli, which represent several types of the most abundant bacterial phyla in the gut. Subsequently, a global and targeted metabolomics approach was used to characterize the metabolomic disruption from TET exposure. The third part of the thesis explored the metabolic consequences of TET exposed gut microbiome secretome that may possibly be linked with host effects such as increased body weight gain. First, an in vitro gut microbiome was established using the fecal matter from a single healthy donor as the inoculum and exposed to multiple doses of TET at two feeding states: fed and fasted. To understand more host relevant effects, this section of the thesis focused on the important gut microbial metabolites with known host health implications, incorporating a targeted approach along with the global metabolomics analysis. This thesis also tentatively explored the contribution of TET altered microbe-host interactions mediated through gut bacterial metabolites and immunoregulatory compounds on obesity-related complications. Particularly, the study investigated the obesity-related complications using an in vitro liver cell model (HepG2) by analyzing the cytotoxic effects and lipid dysregulations upon exposure to TET treated gut microbiome secretome. For the immune response, the study examined the lipopolysaccharides (LPS) levels in the secretome of TET exposed gut microbiome.